Trend Assessment of Different Malariometric Parameters of Surat City: A Retrospective Study (International Journal of Scientific Research and Management (IJSRM), 2017)
Malaria is a life threatening disease caused by parasites of the genus Plasmodium that is transmitted to people through the bites of infected mosquitoes. It is the leading cause of death in children under the age of 5 years and pregnant women, in developing countries. The present study was carried out with secondary data to assess the trend of malaria in terms of various malariometric parameters such as Annual Blood Examination Rate (ABER), Annual Parasite Incidence (API), Slide Positivity Rate (SPR) and Slide Falcifuram Rate (SFR) of Surat City. The analysis has shown that there is an overall declining trend in malaria in the city. The annual blood examination rate has increased from 2001 to 2014. The various malariometric indicators such as API, SPR and SFR have reduced drastically in the last decade This could imply that although there are different malaria control activities each year such as insecticide spraying, elimination of mosquito breeding sites, distribution of Insecticide Treated Nets and malaria drugs to decrease mortality and morbidity of malaria, prevalence is sustained by the continuous vigilance of local governing body that is Surat Municipal Corporation.